Self-repairing gel foam system and preparation method thereof

The self-healing gel foam system constructed by modified starch and nano-SiO2 particles solves the problem of poor stability of traditional foam in high-temperature and high-salt environments, realizes the self-healing of the liquid film and improves the mechanical strength, and adapts to the complex mining conditions of the western gas fields.

CN120699198APending Publication Date: 2025-09-26CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511100993.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Traditional foam drainage gas production technology has poor foam stability in high temperature, high mineralization and high condensate oil environments, cannot meet the long-term production needs of western gas fields, and lacks self-repair capabilities.

Method used

A self-repairing gel foam system composed of modified starch and modified nano-SiO2 particles is used to construct a gas-liquid-solid three-phase stable skeleton by forming a three-dimensional network structure and uniformly distributed nanoparticles, thereby achieving self-repair of the liquid film and enhancing mechanical strength.

Benefits of technology

It significantly improves the foam's anti-interference ability in complex environments, prolongs the foam's survival time, enhances its liquid carrying capacity, adapts to complex conditions such as high temperature, high salinity, and condensate oil, and ensures efficient production of gas wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699198A_ABST
    Figure CN120699198A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing gel foam system and a preparation method thereof. The self-repairing gel foam system is composed of 0.3% of lauryl sodium sulfate, 3% of alpha-starch, 3% of acrylamide monomer, 0.1% of N, N '-methylene bisacrylamide cross-linking agent, 0.2% of potassium persulfate initiator and 0.002% of 30nm nano SiO2 particles modified by 0.05 wt% of fatty alcohol-polyoxyethylene ether. The preparation method comprises the following steps: enabling modified starch, acrylamide and the like to react to form starch gel, adding lauryl sodium sulfate and modified nano SiO2, and stirring to obtain the modified starch gel. Gel macromolecular aggregates in the system form a three-dimensional network structure, nanoparticles are uniformly dispersed on the surface of a liquid film to form a gas-liquid-solid three-phase skeleton, and a self-repairing function is realized through a hydrogen bond dynamic effect, so that bubble coalescence can be inhibited, and the capabilities of resisting hypersalinity, high temperature, gas condensate and methanol are enhanced; the problems that traditional foam is poor in stability and free of self-repairing capacity are solved, and the drainage gas recovery requirements of complex working conditions of western gas fields are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of foam drainage and gas production, and in particular to a self-repairing gel foam system and a preparation method thereof. Background Art

[0002] As an important natural gas producing area, China's western gas fields face the key problem of reduced production capacity due to liquid accumulation in gas wells during development. Due to insufficient energy, the natural gas produced by the gas wells cannot carry formation water and condensate to the surface, resulting in liquid accumulation at the bottom of the well. In severe cases, it leads to flooding or production suspension. Foam drainage gas production technology is the core means to solve this problem. It injects foaming agents to form foam with water, reducing the liquid density to enhance the liquid carrying capacity of the gas flow. However, western gas fields generally have complex conditions such as high temperature (up to 90°C), high mineralization (up to 250,000 mg / L), condensate oil and methanol. The foam stability of traditional foaming agents decreases significantly in such environments, and the foaming ability and liquid carrying efficiency are greatly reduced, making it difficult to meet on-site needs. Therefore, the development of a self-healing gel foam system that can maintain excellent performance in complex media is of great practical significance to ensure the efficient development of western gas fields.

[0003] Traditional foam drainage technology primarily relies on single surfactants (such as sodium lauryl sulfate) or simple compound systems. The core principle is to use surfactants to reduce gas-liquid interfacial tension, forming foam that carries the accumulated fluid. The advantages of this technology lie in its simple formulation, low cost, and short-term effectiveness in conventional gas wells at room temperature and low salinity.

[0004] However, these systems also have significant drawbacks: First, they are weak in their ability to withstand environmental interference. Surfactants are easily decomposed at high temperatures, and high mineralization can destroy the foam's double-layer structure, leading to rapid foam collapse. Second, they lack stability. Traditional foam films are thin (usually less than 1 μm) and easily coalesce when disturbed by airflow or contaminated by condensate oil, with a half-life of less than 5 minutes. Third, they lack self-repairing capabilities. Once the film ruptures, it cannot be restored, making it difficult to adapt to long-term production needs. Furthermore, traditional systems lack solid stabilizers, resulting in low foam skeleton strength and easy destruction in high-oil or high-methanol environments, making them unable to meet the continuous liquid-carrying requirements of the complex working conditions of western gas fields.

[0005] In recent years, the industry has developed two types of improvement solutions to address the shortcomings of traditional technologies: one is to use a compound of polymers (such as partially hydrolyzed polyacrylamide) and surfactants to enhance foam stability by increasing the viscosity of the liquid phase; the other is to introduce nanoparticles (such as unmodified SiO2) as foam stabilizers, using the adsorption effect of particles at the interface to delay liquid film drainage.

[0006] While existing technologies have improved foam performance to a certain extent, their limitations remain significant: polymer compound systems can increase viscosity, but are susceptible to thermal oxidative degradation at high temperatures, and high mineralization causes polymer molecular chains to curl up, significantly reducing foam stabilization effectiveness. Unmodified nanoparticles, due to their highly hydrophilic surface, tend to aggregate in aqueous solutions and are difficult to evenly disperse at the gas-liquid interface, resulting in limited actual foam stabilization. Furthermore, existing technologies fail to address the self-repairing problem of foams; the liquid film cannot be rebuilt after rupture, and their tolerance to condensate oil is insufficient (the foam half-life decreases by more than 50% when the oil content exceeds 20%), making them unable to meet the stringent conditions of western gas fields. Summary of the Invention

[0007] Based on the above technical problems, the present application discloses a self-repairing gel foam system and a preparation method, wherein the self-repairing gel foam system specifically comprises 0.3% sodium dodecyl sulfate, 3% modified starch, 3% acrylamide monomer, 0.1% N,N'-methylenebisacrylamide crosslinker, 0.2% potassium persulfate initiator and 0.002% modified nano-SiO2 particles, wherein the modified nano-SiO2 particles are 30nm self-dispersed nano-SiO2 particles with partial hydrophobicity that are physically modified with 0.05wt% fatty alcohol polyoxyethylene ether; in the self-repairing gel foam system, the gel macromolecular aggregates form a three-dimensional network structure, and the nanoparticles are uniformly dispersed on the surface of the liquid film to form a gas-liquid-solid three-phase stable skeleton.

[0008] Preferably, the modified starch is α-starch, which is hydrolyzed and polymerized with acrylamide monomer under the action of potassium persulfate initiator. The formed high molecular weight polymer product PCP undergoes dehydration condensation reaction with N,N'-methylenebisacrylamide crosslinker to form intermolecular and intramolecular crosslinks.

[0009] Preferably, the surface of the modified nano-SiO2 particles contains hydroxyl groups, and the fatty alcohol polyoxyethylene ether is modified on the surface of the SiO2 particles by physical adsorption and chemical grafting with the hydroxyl groups, and the modified nano-SiO2 particles are uniformly dispersed on the surface of the foam liquid film.

[0010] Preferably, the foam liquid film has a thickness of 5 μm, the average radius of a single bubble is 25 μm, the nanoparticles on the surface of the foam liquid film are distributed in a uniform array, and the solid film formed can inhibit bubble aggregation and disproportionation.

[0011] Preferably, the three-dimensional network structure is formed by the agglomeration of intermolecular crosslinkers and intramolecular crosslinkers through high-speed mechanical shearing, and is a nano-scale spherical gel macromolecular aggregate with a large number of hydroxyl groups exposed on its surface; the modified nano-SiO2 particles interact with the hydroxyl groups of the gel macromolecular aggregates through hydrogen bonds to form a continuous composite protective layer on the surface of the foam liquid film.

[0012] A method for preparing a self-repairing gel foam system, comprising:

[0013] S1. 3% modified starch, 3% acrylamide monomer, 0.1% N,N'-methylenebisacrylamide crosslinker, and 0.2% potassium persulfate initiator were added to deionized water in sequence, stirred evenly, and then heated in an 80°C constant temperature box for 30 minutes to form a starch gel;

[0014] S2. Add 0.3% sodium lauryl sulfate to the starch gel and stir until completely dissolved to obtain a mixed solution;

[0015] S3, add 0.002% of 30nm nano-SiO2 particles modified with fatty alcohol polyoxyethylene ether into the mixture of S2 and stir evenly;

[0016] S4. Pour the solution obtained in S3 into a corrugated stirrer and stir at 10,000 rpm for 5 minutes to obtain a self-repairing gel foam system.

[0017] Preferably, the hydrolysis of the modified starch in S1 is specifically as follows: two hydroxyl groups are generated by breaking the ether bond in the six-membered ring of α-starch, and the polymerization reaction between the hydrolyzed starch molecules and acrylamide monomers is initiated under the action of potassium persulfate initiator, and the reaction time is controlled within 30 minutes.

[0018] Preferably, the addition of sodium lauryl sulfate in S2 needs to be carried out when the starch gel temperature drops below 45° C. to prevent high temperature from destroying the molecular structure of the surfactant and affecting the foaming performance.

[0019] Preferably, the modification of the nano-SiO2 in S3 is specifically as follows: 0.06g of dry SiO2 powder is taken, the solid content is adjusted to 0.0025wt%, and after stirring for 1h, 0.15g of fatty alcohol polyoxyethylene ether is added in a 70°C water bath, and stirring is continued for 2h to complete the modification.

[0020] Preferably, the stirring rate of the corrugated stirrer in S4 needs to be gradually increased to 10,000 rpm to avoid excessive stirring in the initial stage resulting in uneven bubble size, and the foam volume and half-life are measured immediately after the stirring is completed.

[0021] Compared with the prior art, the technical solution of this application has the following technical effects:

[0022] The self-repairing gel foam system of the present invention forms a three-dimensional network structure through gel macromolecular aggregates, combined with the uniform array distribution of modified nano-SiO2 particles on the liquid film surface, to construct a stable gas-liquid-solid three-phase skeleton. The structure can effectively inhibit bubble aggregation and disproportionation, slow down the liquid film drainage speed, significantly improve the foam's anti-interference ability in complex environments, avoid rapid foam rupture due to external disturbances, and prolong the foam's survival time.

[0023] In the system of the present invention, the hydroxyl groups on the surface of the gel macromolecular aggregates and the modified nano-SiO2 particles dynamically interact through hydrogen bonds to form a reversibly bonded composite protective layer. When the foam liquid film is locally damaged, the surrounding gel molecules and nanoparticles can quickly migrate to the damaged area and rebuild a stable structure, so that the broken liquid film can be repaired, solving the problem that traditional foam cannot be restored once it is damaged.

[0024] The nano-SiO2 particles modified with fatty alcohol polyoxyethylene ethers in this invention have optimized surface properties, resisting ion interference and preventing agglomeration in highly mineralized environments. Furthermore, the three-dimensional gel network structure exhibits excellent thermal stability, can withstand high temperatures, and is not susceptible to media such as condensate and methanol, ensuring the system maintains stable performance in a variety of complex media.

[0025] The foam liquid film formed by the system of the present invention has uniform thickness and regular distribution of single bubble sizes. The plateau interface between adjacent bubbles can effectively retain surfactants and reduce liquid film loss. This orderly structural morphology improves the mechanical strength of the foam, allowing it to maintain its intact shape under dynamic conditions such as airflow impact, thereby enhancing the foam's liquid carrying capacity and application reliability.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application so that it can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following is a detailed description of the preferred embodiment of the present application in conjunction with the accompanying drawings.

[0027] Based on the detailed description of the specific embodiments of the present application in conjunction with the accompanying drawings below, those skilled in the art will become more aware of the above and other objects, advantages and features of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following will briefly introduce the drawings required for the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without inventive work. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0029] According to the description of the drawings in the document and the corresponding technical content, the titles of the drawings are as follows:

[0030] Figure 1 This is a SEM schematic electron microscope image of nano-SiO2 particles;

[0031] Figure 2This is a microscopic electron microscope image of the self-healing gel foam;

[0032] Figure 3 Flowchart for the preparation of self-healing gel-foam system. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. In the following description, specific details such as specific configurations and components are provided only to help fully understand the embodiments of the present application. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for clarity and brevity, the description of known functions and structures has been omitted in the embodiments.

[0034] It should be understood that references throughout this specification to "one embodiment" or "this embodiment" mean that a particular feature, structure, or characteristic associated with the embodiment is included in at least one embodiment of the present application. Therefore, the appearance of "one embodiment" or "this embodiment" throughout this specification does not necessarily refer to the same embodiment. Furthermore, these particular features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.

[0035] In addition, the present application may repeat reference numerals and / or letters in different examples. This repetition is for the purpose of simplicity and clarity and does not in itself indicate the relationship between the various embodiments and / or settings discussed.

[0036] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that three relationships can exist. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association object relationship, indicating that two relationships can exist. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the previous and subsequent associated objects are in an "or" relationship.

[0037] The term "at least one" in this article is merely a description of the association relationship between associated objects, indicating that three relationships may exist. For example, at least one of A and B can mean: A exists alone, A and B exist at the same time, and B exists alone.

[0038] It should also be noted that, in this document, relational terms such as first and second are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include," "comprises," or any other variations thereof are intended to cover non-exclusive inclusion.

[0039] Example 1

[0040] This embodiment mainly describes the structure of a self-repairing gel foam system, specifically:

[0041] The self-repairing gel foam system is composed of 0.3% sodium dodecyl sulfate (SDS), 3% modified starch (α-starch), 3% acrylamide (AM) monomer, 0.1% N,N'-methylenebisacrylamide crosslinker, 0.2% potassium persulfate initiator and 0.002% modified nano-SiO2 particles; wherein the modified nano-SiO2 particles are 30nm monodisperse spherical SiO2 physically modified with 0.05wt% fatty alcohol polyoxyethylene ether (AEO), such as Figure 1 As shown, the hydrophobic ends of the AEO molecules adsorb to the SiO2 surface via van der Waals forces, with the hydrophilic ends facing outward. Simultaneously, ether bonds form weak chemical grafts with the SiO2 surface hydroxyl groups, enhancing the particle's hydrophobicity while preventing aggregation. This modification enables the nanoparticles to be stably dispersed in the system, forming a synergistic effect with other components. The SDS reduces the gas-liquid interfacial tension and promotes foaming, the gel network provides structural support, and the nanoparticles enhance the liquid film's strength, collectively forming the core structural foundation of the system.

[0042] Furthermore, in the self-repairing gel foam system, α-starch breaks the six-membered ring ether bond through hydrolysis reaction to generate small molecular fragments containing free hydroxyl groups. Subsequently, the hydrolyzed starch and AM monomer undergo polymerization reaction under the action of potassium persulfate initiator to form a high molecular weight polymer product PCP; PCP then undergoes dehydration condensation with N,N'-methylenebisacrylamide crosslinker to generate intermolecular and intramolecular crosslinks. The crosslinked body agglomerates through high-speed mechanical shearing to form nano-scale spherical gel macromolecular aggregates, which are interconnected to form a three-dimensional network structure. Its microscopic morphology is as follows: Figure 2 As shown, the network skeleton is composed of a fibrous structure with a diameter of 50-100 nm and a uniform pore size (200-500 nm). This structure provides rigid support for the foam while retaining sufficient space to accommodate gas to form bubbles.

[0043] Furthermore, the surface of the modified nano-SiO2 particles is rich in hydroxyl groups, which interact strongly with the hydroxyl groups on the surface of the gel macromolecular aggregates through hydrogen bonds. This effect makes the nanoparticles evenly dispersed on the surface of the foam liquid film, forming a continuous "gel-nano" composite protective layer. It can be seen that 30nm nanoparticles are distributed in a regular array on the surface of the liquid film, with a particle spacing of about 50nm and no obvious agglomeration. This distribution makes the liquid film thickness reach 5μm, which is much larger than the traditional foam liquid film (usually less than 1μm), significantly improving the mechanical strength and anti-rupture ability of the liquid film. At the same time, the presence of nanoparticles can inhibit the liquid film drainage speed, reduce the probability of bubble aggregation and disproportionation, and lay the foundation for the stability of the system.

[0044] Furthermore, the bubbles formed by the self-healing gel foam system after foaming have a uniform size distribution, with an average radius of 25μm per bubble. The bubbles are independently dispersed, separated by liquid films, and have no significant adhesion. A plateau junction region forms at the interface between the liquid films of adjacent bubbles. This region, due to surface tension differences, accumulates a high concentration of SDS molecules. This Marangoni effect slows down liquid film drainage and further enhances foam stability. The ratio of the liquid film thickness (5μm) to the bubble radius (25μm) is approximately 1:5. This ratio enables the liquid film to effectively resist external pressure changes and airflow disturbances, ensuring that the bubbles maintain their intact form in complex environments.

[0045] Furthermore, the hydrogen bonding between the hydroxyl groups on the surface of the gel macromolecular aggregates and the nanoparticles is dynamically reversible. When the foam liquid film is locally ruptured due to external impact, the gel molecules and nanoparticles in the surrounding area can quickly migrate to the damaged area driven by hydrogen bonding, rebuild a stable composite protective layer, and realize the self-repair of the liquid film. This mechanism is combined with the elastic deformation ability of the gel three-dimensional network. When the bubbles are squeezed, the network structure can deform moderately to absorb energy and avoid direct rupture of the liquid film. At the same time, the directional arrangement of SDS at the gas-liquid interface can quickly replenish the surfactant molecules lost due to the rupture of the liquid film and maintain the stability of the interfacial tension. The synergistic effect of the three enables the system to maintain good structural stability under complex conditions such as high temperature, high salt, and condensate oil, reflecting excellent self-healing performance and environmental adaptability.

[0046] This example describes a self-healing gel foam system. Leveraging the synergistic hydrogen bonding between 30nm modified nano-SiO2 and the gel network, it forms a 5μm-thick liquid film and a stable three-dimensional structure, significantly enhancing its resistance to rupture. Its self-healing mechanism rapidly fills film defects, maintaining foam stability in environments with high salinity, high temperatures, and condensate, significantly extending its half-life and providing excellent foaming performance, making it adaptable to complex operating conditions.

[0047] Example 2

[0048] This embodiment describes in detail a method for preparing a self-repairing gel foam system. Figure 3 As shown, specifically including:

[0049] S1. 3% modified starch, 3% acrylamide monomer, 0.1% N,N'-methylenebisacrylamide crosslinker, and 0.2% potassium persulfate initiator were added to deionized water in sequence, stirred evenly, and then heated in an 80°C constant temperature box for 30 minutes to form a starch gel;

[0050] S2. Add 0.3% sodium lauryl sulfate to the starch gel and stir until completely dissolved to obtain a mixed solution;

[0051] S3, adding 0.002% of 30nm nano-SiO2 particles modified with fatty alcohol polyoxyethylene ether to the mixture obtained in S2 and stirring evenly;

[0052] S4. Pour the solution obtained in S3 into a corrugated stirrer and stir at 10,000 rpm for 5 minutes to obtain a self-repairing gel foam system.

[0053] Furthermore, the hydrolysis of the modified starch in S1 is specifically as follows: two hydroxyl groups are generated by breaking the ether bond in the hexacyclic ring of α-starch, and the polymerization reaction of the hydrolyzed starch molecules and acrylamide monomers is initiated under the action of potassium persulfate initiator, and the reaction time is controlled within 30 minutes.

[0054] Furthermore, the addition of sodium lauryl sulfate in S2 needs to be carried out when the starch gel temperature drops below 45°C to prevent high temperature from destroying the molecular structure of the surfactant and affecting the foaming performance.

[0055] Furthermore, the modification of nano-SiO2 in S3 was carried out as follows: 0.06 g of dry 30 nm nano-SiO2 powder was taken, deionized water was added to adjust the solid content to 0.0025 wt%, and a magnetic stirrer was used to stir at a rate of 500 r / min for 1 h to make the SiO2 preliminarily dispersed. The solution was then transferred to a 70 ° C water bath, 0.15 g of fatty alcohol polyoxyethylene ether (AEO, concentration 0.05 wt%) was added, and the modification was completed by continuous stirring for 2 h; AEO was modified by physical adsorption and chemical bonding. The surface of SiO2 is modified by branching: the hydrophobic end is adsorbed on the hydroxyl group of the SiO2 surface through van der Waals force, the hydrophilic end faces outward, and the ether bond forms a weak chemical bond with the hydroxyl group; the dispersibility of the modified nano-SiO2 particles needs to be verified by dynamic light scattering, and the particle size distribution should be concentrated at 30±5nm, with no obvious agglomeration peak. Then 0.002% modified nano-SiO2 particles are added to the mixed solution obtained by S2, and stirred at 400r / min at 70°C for 2h to ensure that the particles are evenly dispersed in the system.

[0056] Furthermore, in S4, the solution obtained in S3 is poured into a corrugated stirrer. The stirring rate needs to be increased in stages. Initially, it is stirred at 3000r / min for 1 minute to achieve preliminary mixing of the system; then it is stirred at 5000r / min for 2 minutes to promote bubble nucleation; finally, it is gradually increased to 10000r / min and stirred for 2 minutes to complete foaming. This operation can avoid the uneven bubble size caused by the initial high-speed stirring; after the stirring is completed, the foam is immediately transferred to a 1000mL graduated cylinder, the initial foam volume (foaming power) is measured, and the time for the foam to precipitate 100mL of liquid (half-life) is recorded. The foam microstructure is observed by scanning electron microscopy (SEM), which shows that the nano-SiO2 particles are distributed in an array on the surface of the liquid film. The liquid film thickness reaches 5μm, and the average radius of a single bubble is 25μm.

[0057] This example describes in detail the preparation method of a self-healing gel foam system. By precisely controlling the hydrolysis and polymerization reaction time of α-starch to avoid excessive cross-linking of the system, SDS is added below 45°C to ensure its interfacial activity. The AEO-modified nano-SiO2 is evenly dispersed and synergistically acts with the gel network. The stirring rate is increased in stages to ensure uniform bubble size. The resulting self-healing gel foam system has a stable liquid film structure, nanoparticles form an effective protective layer, good self-healing ability, and can adapt to complex media environments.

[0058] The above are only preferred embodiments of the present invention, which do not limit the scope of protection of the present invention. For those skilled in the art, the present invention can be modified and varied in various ways. Any changes, modifications, replacements, integrations and parameter changes to these embodiments through conventional substitutions or that can achieve the same functions without departing from the principles and spirit of the present invention fall within the scope of protection of the present invention.

Claims

1. A self-repairing gel foam system, characterized in that: The self-repairing gel foam system comprises 0.3% sodium lauryl sulfate, 3% modified starch, 3% acrylamide monomer, 0.1% N,N'-methylenebisacrylamide crosslinking agent, 0.2% potassium persulfate initiator and 0.002% modified nano-SiO2 particles, wherein the modified nano-SiO2 particles are 30nm self-dispersed nano-SiO2 particles with partial hydrophobicity that are physically modified with 0.05wt% fatty alcohol polyoxyethylene ether; in the self-repairing gel foam system, gel macromolecular aggregates form a three-dimensional network structure, and nanoparticles are uniformly dispersed on the surface of the liquid film to form a gas-liquid-solid three-phase stable skeleton.

2. A self-repairing gel foam system according to claim 1, characterized in that: The modified starch is α-starch, which undergoes polymerization reaction with acrylamide monomer under the action of potassium persulfate initiator after hydrolysis. The formed high molecular weight polymer product PCP undergoes dehydration condensation reaction with N,N'-methylenebisacrylamide crosslinking agent to generate intermolecular and intramolecular crosslinked bodies.

3. The self-repairing gel foam system according to claim 1, characterized in that: The modified nano-SiO2 particles contain hydroxyl groups on their surfaces, and the fatty alcohol polyoxyethylene ether is modified on the SiO2 particle surfaces by physical adsorption and chemical grafting with the hydroxyl groups, and the modified nano-SiO2 particles are uniformly dispersed on the surface of the foam liquid film.

4. A self-repairing gel foam system according to claim 1 or 4, characterized in that: The thickness of the foam liquid film is 5μm, the average radius of a single bubble is 25μm, and the nanoparticles on the surface of the foam liquid film are evenly distributed in an array. The solid film formed can inhibit bubble aggregation and disproportionation.

5. The self-repairing gel foam system according to claim 1, characterized in that: The three-dimensional network structure is formed by the agglomeration of intermolecular crosslinking bodies and intramolecular crosslinking bodies through high-speed mechanical shearing, and is a nano-scale spherical gel macromolecular aggregate with a large number of hydroxyl groups exposed on its surface; the modified nano-SiO2 particles interact with the hydroxyl groups of the gel macromolecular aggregates through hydrogen bonds to form a continuous composite protective layer on the surface of the foam liquid film.

6. A method for preparing a self-repairing gel foam system, applicable to the self-repairing gel foam system according to any one of claims 1 to 5, characterized in that: include: S1. 3% modified starch, 3% acrylamide monomer, 0.1% N,N'-methylenebisacrylamide crosslinker, and 0.2% potassium persulfate initiator were added to deionized water in sequence, stirred evenly, and then heated in an 80°C constant temperature box for 30 minutes to form a starch gel; S2. Add 0.3% sodium lauryl sulfate to the starch gel and stir until completely dissolved to obtain a mixed solution; S3, add 0.002% of 30nm nano-SiO2 particles modified with fatty alcohol polyoxyethylene ether to the mixed solution of S2 and stir evenly; S4. Pour the solution obtained in S3 into a corrugated stirrer and stir at 10,000 rpm for 5 minutes to obtain a self-repairing gel foam system.

7. The method for preparing a self-repairing gel foam system according to claim 6, characterized in that: The hydrolysis of the modified starch in S1 is specifically as follows: two hydroxyl groups are generated by breaking the ether bond in the six-membered ring of α-starch, and the polymerization reaction between the hydrolyzed starch molecules and acrylamide monomers is initiated under the action of potassium persulfate initiator, and the reaction time is controlled within 30 minutes.

8. The method for preparing a self-repairing gel foam system according to claim 6, characterized in that: The addition of sodium lauryl sulfate in S2 needs to be carried out when the starch gel temperature drops below 45° C. to prevent high temperature from destroying the molecular structure of the surfactant and affecting the foaming performance.

9. The method for preparing a self-repairing gel foam system according to claim 6, characterized in that: The modification of the nano-SiO2 in S3 is specifically as follows: 0.06g of dry SiO2 powder is taken, the solid content is adjusted to 0.0025wt%, and after stirring for 1h, 0.15g of fatty alcohol polyoxyethylene ether is added in a 70°C water bath, and stirring is continued for 2h to complete the modification.

10. The method for preparing a self-repairing gel foam system according to claim 6, characterized in that: The stirring rate of the corrugated stirrer in S4 needs to be gradually increased to 10,000 rpm to avoid excessive stirring in the initial stage, which may lead to uneven bubble size. The foam volume and half-life are measured immediately after the stirring is completed.